2013
DOI: 10.1161/atvbaha.112.300748
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated Low-Density Lipoprotein Induces LRP1 Stabilization Through E3 Ubiquitin Ligase CHFR Downregulation in Human Vascular Smooth Muscle Cells

Abstract: Objective-Low density lipoprotein retention and aggregation in the arterial intima are key processes in atherogenesis. Aggregated LDL (agLDL) is taken up through low-density lipoprotein receptor-related protein 1 (LRP1) by human vascular smooth muscle cells (VSMC). AgLDL increases LRP1 expression, at least in part, by downregulation of sterol regulatory element-binding proteins. It is unknown whether agLDL has some effect on the ubiquitin-proteasome system, and therefore on the LRP1 receptor turnover. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…As expected, LRP1 WT levels decreased progressively with a half-life of >24 hours. 26 In contrast, the half-life of p.Val3244Ile mutant was ≈50% and of the p.Glu3983Asp ≈85% shorter compared with WT (Figure 1 E). In an attempt to restore the mutant LRP1 expression, transiently transfected cells were cultured at lower temperature (30°C), which has been previously shown to improve protein folding and subsequently stability.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…As expected, LRP1 WT levels decreased progressively with a half-life of >24 hours. 26 In contrast, the half-life of p.Val3244Ile mutant was ≈50% and of the p.Glu3983Asp ≈85% shorter compared with WT (Figure 1 E). In an attempt to restore the mutant LRP1 expression, transiently transfected cells were cultured at lower temperature (30°C), which has been previously shown to improve protein folding and subsequently stability.…”
Section: Resultsmentioning
confidence: 88%
“…Such studies may benefit from a focus on those exons encoding for the domains involved in the uptake of CTSD (ie, exons 83–84). 26 Further support may come from in vitro studies showing that decreased ABCA1 at the cell membrane because of LRP1 downregulation is associated with reduced cholesterol efflux to apoA1. In addition, downregulation of LRP1 in human hepatic cell lines may help to study the anticipated increased SR-B1–mediated uptake of cholesteryl ester from HDL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the pharmacological activation of PPARγ promotes its own proteolytic degradation via UPS ( Hauser et al, 2000 ; Kilroy et al, 2009 ). In addition, it has been proposed that UPS is the key regulator for LRP1 degradation in a number of cell lines, including HepG2 ( Melman et al, 2002 ; Cal et al, 2013 ). The use of MG132, a potent UPS inhibitor, in HepG2 cells treated with RGZ (30 μM) for 24 h did not prevent LRP1 protein degradation, as shown in Figure 2C .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, LRP1 can mediate uptake of aggregated LDL and subsequent cholesterol accumulation in VSMC. Aggregated LDL seems to stabilize LRP1 and increase its expression by decreasing ubiquitin-mediated degration (240). VSMC-specific deficiency of LRP1 in LDLR-null mice resulted in thickening of the media, dilation of the aorta, aneurysm formation, and accelerated atherosclerosis (191).…”
Section: Newer Insights Into the Role Of Vsmc In Atherosclerosismentioning
confidence: 99%